A integração do negro no Brasil: raça ou classe? Uma busca teórica e histórica a partir de Florestan Fernandes - Nery, Jonatas Correa (2019)
The present work is the result of a theoretical and historical research, based on Florestan Fernandes's book, “The negro in brazillian society” (1969). It treats as the central theme the theoretical understandings about race and class, trying to situate one and the other debate (race and class), from the already consolidated readings on the theme. Although the research was based on the analysis of the work itself, the development of the work resorted to the class debate with the Marxist authors, but with particular attention to the writings of Karl Marx himself. Similarly, and in parallel, went to history to understand how race arises as a differentiator or classifier of different human groups around the planet, always correlating with the Marxian analytical method. Evidently this path was not by chance. It arises as a demand of the research itself. The generating hypothesis was the statement, derived from Hasenbalg (1979), that Florestan Fernandes, besides treating the racial issue as an effect of “cultural delay”, subsumes race in class. That is, it indicates that race due to the process of capitalism development would no longer be a relevant element of differentiation. Therefore, the research aimed to analyze how it appears and are made the theoretical developments of race and class in the work "The negro in brazillian society". In order to attend to the object it was necessary, therefore, to understand what is race and what is class, and only then deal with the data concerning the integration of black people in brazillian society. The result of the research was that the statement made may have been the result of an analysis perhaps foreign to dialectical reading, since Fernandes never abandoned race as a significant element in explaining differences, even within the capitalist system. On the contrary, it concludes that the black people has become in Brazil an “index element” to gauge the kind of democracy one experiences.